Study of ionization and ion transfer rates in flowing N2 DC discharges and post-discharges. (28th September 2021) - Levaton, J; Klein, A N; Amorim, J; Severo, J H F
Abstract: In this work, we studied the ionization and ion transfer rates in flowing nitrogen DC discharges and post-discharges. Two different experimental set-ups and conditions for the flowing nitrogen discharges were analyzed. The first experimental set-up includes a post-discharge tube where the pink afterglow phenomenon was detected. Two well-established discharge and post-discharge kinetic numerical models we had previously developed to study the nitrogen flowing DC discharges and post-discharges were employed to calculate the rates for our experimental conditions. We analyzed 18 ionization and nine ion transfer mechanisms for N +, N2 +, N3 +, and N4 + ions in the discharges and post-discharges. We observed that the electron density of the discharges, which varies by one order of magnitude, plays a major role in the rates behavior for the two experimental set-ups. Moreover, we observed that the rates found in the pink afterglow phenomenon are relevant when compared to rates found in the discharges. The important role of molecular metastable Penning ionization and atoms and molecules associative ionization appear in the ionization rates of the discharges. It is also shown that ion transfer mechanisms play a crucial role in the ions densities distribution found in the discharges and post-discharges. This work brings an original comparative study of ionization and ion transfer rates for experimental flowing nitrogen DC positive columns and pink afterglow post-discharge. This is the first time that a detailed combined experimental and theoretical analysis on the ionization and ion transfer rates is carried out for nitrogen flowing DC positive columns and pink afterglow plasma.